1976
DOI: 10.1152/ajplegacy.1976.231.2.408
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory adrenal growth: a neurally mediated reflex

Abstract: The responses of young rats to left adrenalectomy or left adrenal manipulation were compared to surgical sham adrenalectomy in which adrenals were observed but not touched. At 12 h right adrenal wet weight, dry weight, DNA, RNA, and protein content were increased (P less than 0.05) after the first two operations. Left adrenal manipulation resulted in increased right adrenal weight at 12 h but no change in left adrenal weight. Sequential manipulation of the left adrenal at time 0 and the right adreanl at 12 h r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 0 publications
3
34
0
Order By: Relevance
“…The procedure in which one adrenal is surgically removed results in a rapid increase (within 24 h) in the size of the contralateral gland as measured by an increase in wet weight, and DNA and RNA synthesis. The mechanisms that regulate the process have been investigated extensively, and it has been demonstrated that a neural circuit exists involving the hypothalamus which when stimulated by manipulation of one adrenal stimulates growth of the other gland (Dallman et al 1976(Dallman et al , 1980. Despite the neural involvement, there is a still a requirement for the pituitary because, although compensatory growth does occur in hypophysectomised animals, it is against the background of a gland undergoing rapid adrenal atrophy and appears more of a slowing of this atrophy rather than any increase in size (Dallman et al 1980).…”
Section: Compensatory Adrenal Growthmentioning
confidence: 99%
“…The procedure in which one adrenal is surgically removed results in a rapid increase (within 24 h) in the size of the contralateral gland as measured by an increase in wet weight, and DNA and RNA synthesis. The mechanisms that regulate the process have been investigated extensively, and it has been demonstrated that a neural circuit exists involving the hypothalamus which when stimulated by manipulation of one adrenal stimulates growth of the other gland (Dallman et al 1976(Dallman et al , 1980. Despite the neural involvement, there is a still a requirement for the pituitary because, although compensatory growth does occur in hypophysectomised animals, it is against the background of a gland undergoing rapid adrenal atrophy and appears more of a slowing of this atrophy rather than any increase in size (Dallman et al 1980).…”
Section: Compensatory Adrenal Growthmentioning
confidence: 99%
“…Dallman (16) distinguishes four types of adrenal cortex growth and each of them is differentially regulated. Enucleation-induced adrenocortical regeneration resembles growth of the gland at early embryogenesis and depends on several neural and endocrine signals (17)(18)(19)(20)(21), while unilateral adrenalectomy-induced compensatory growth is primarily neurally mediated (16,(22)(23)(24)(25). Adrenocortical growth related to maturation is probably regulated by numerous growth factors while adrenocorticotropic hormone (ACTH)-induced growth primarily depends on adrenocortical cell proliferation (16,26).…”
Section: Introductionmentioning
confidence: 99%
“…21 and 22). Also, neural inputs seem to mediate compensatory growth in the remaining adrenal after unilateral adrenalectomy (23). The sympathoadrenomedullary system produces these effects on the adrenal cortex in part by increasing sensitivity to ACTH.…”
mentioning
confidence: 99%